The Relationship Between Risk Factor Obesity in Pregnancy with the Incidence of Caesarean Delivery: Literature Review - Desak Putu Eka Heny Hayudha; Farida Fitriana; Ni Wayan Suarniti (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
The obesity rate in Indonesia has increased from 14.8% to 21.8% from 2013 to 2018. Especially obesity in pregnancy is a problem that can threaten pregnancy until delivery and become one of the risk factors associated with caesarean delivery. The results of research in America state that almost 50% of cesarean deliveries are women who are overweight or obese before pregnancy. This type of research uses literature review. This literature review seeks to establish the correlation between the risk factors associated with obesity during pregnancy and the occurrence of cesarean delivery.. The method of searching articles or journals using boolean operators and keywords (OR NOT, AND or AND NOT). The selection criteria employed encompassed articles that were available in their entirety via national and international database searches, spanning the period of the past decade (2010-2020). The results based on a literature review of 8 journals found that 6 of the 8 articles stated that there was an association between the risk factors of obesity in pregnancy with the incidence of cesarean delivery, Contrary to the previous two papers, our findings indicate that there is no connection between the likelihood of cesarean delivery and obesity in women. The literature study concludes that there is a correlation between obesity during pregnancy and the occurrence of cesarean birth. Although it is necessary to conduct more primary research related to this topic.